INVESTIGATION OF PURE AND SBS MODIFIED BITUMINOUS BINDER PROPERTIES AFTER SHORT TERM AGEING BY USING TWO DIFFERENT AGEING METHODS - Yilmaz, Mehmet; Ahmedzade, Perviz (Gazi Univ, Fac Engineering Architecture, 2008)
In this study Thin Film Oven Test (TFOT) and Rolling Thin Film Oven Test (RTFOT) methods which are the most common methods used to reflect binders short term ageing in laboratory conditions were compared. Four different ratios of Styrene-Butadiene-Styrene (SBS) (1.5%; 3.0%; 4.5% and 6.0%) were added to B 160/220 main bitumen to prepare modified binders. Pure and modified binders were aged with TFOT and RTFOT methods. Penetration and softening point tests were applied to unaged binders and binders aged by TFOT and RTFOT methods. Furthermore thermal sensitivity of binders and mass loss occurring by the effect of ageing were determined. From obtained results it was determined that softening point values were increased and penetration and thermal sensitivity were decreased with rising SBS content before and after ageing. According to results of both methods, it can be said that occurred ageing, mass loss and softening point values of binders aged by TFOT was found to be higher; penetration values to be lower; temperature sensitivity to be same in comparison with values of binders aged by RTFOT.
Keywords: Ageing; modification; RTFOT; TFOT; SBS